KOMITMEN PROFESI SEBAGAI PEMEDIASI HUBUNGAN ETIKA KERJA ISLAM DENGAN KOMITMEN ORGANISASI (Studi Empiris Perbankan Wilayah Kedu) - Zubadi, Hamron (Universitas Muhammadiyah Magelang, 2008)
The objects of this research included managers working in regional banking of Kedu (Wono sobo, Temanggung, Magelang, Purworejo, and Kebumen). The samples were taken by using a non probability sampling method taht is a purposive sampling so that 40 respondents were gained. The hypotheses were analyzed by means of multiple regression and path analyses. The results show that Islamic Working Ethics (accounting, justice, and truth) do not affect proffesional commitment. Islamic Working Ethics (accounting, justice, and truth) do not affect organizational commitment mediated by proffesional commitment. Te result of this research can not support the results of the previous inquiries revealing taht Islamic Working Ethics (Dimension of accountability, justice and truth) positively significantly affect the organizational commitment of the managers. The results of path analysis indicate that proffesional commitment is not an intervening variable, the total (correlation Islamic Working Ethics to organizational commitment) is negative. The total value of negative effects shows additional proffessional commitment variable as the intervening variable can not explain the relationship betwee Islamic Working Ethics and organizational commitment. The results of F test show that Islamic Working Ethics and professional commitment simultaneously bring significant effect on organizational commitment.